Transformational Leadership, Organizational Culture, and Compensation Effects on Job Satisfaction and Performance at BSI Jakarta - Widhi Wicaksono; Azhar Affandi (International Journal of Sharia Business Management, 2026)
This study aims to analyze the influence of transformational leadership, organizational culture, and compensation on employee job satisfaction and performance at Bank Syariah Indonesia (BSI) DKI Jakarta Branch. The method used is a quantitative approach with a descriptive and explanatory design, and data analysis using Structural Equation Modeling (SEM) through the Smart PLS 3.0 application. The results show that transformational leadership has a significant positive influence on employee performance with a value of 76.7%. Organizational culture contributes significantly to job satisfaction by 86.8%, but does not directly affect performance. Compensation is proven to influence employee performance by 25.9%, although it does not significantly affect job satisfaction. In addition, job satisfaction does not have a direct influence on employee performance. Based on these findings, it is recommended to improve transformational leadership and a conducive organizational culture to improve employee performance at BSI. This study contributes to the understanding of factors that influence job performance and satisfaction, and provides suggestions for better human resource management in the future.